Optimization of the Karanganyar Police Criminal Investigation Unit in Handling the Criminal Action of Aggravated Theft for Fair Law Enforcement (Advances in Police Science Research Journal, 2024)
Legal assistance is a human right that cannot be eliminated. The State of Indonesia as a constitutional state is obliged to protect and guarantee legal assistance as respect for human rights. The purpose of this study is to describe the investigative process related to the implementation of the investigator's obligations to provide legal assistance to suspects of theft crime by weighting and find efforts to optimize investigations through legal assistance models to realize fair law enforcement in the Karanganyar Police area. This research is a qualitative research with a field research approach by collecting data through interviews, observation and document study. The respondents included the Head of the Satreskrim Unit of the Karanganyar Police, the suspect in the crime of weighted theft and legal advisers at the legal aid post. The theories used include rule of law theory, law enforcement effectiveness theory, and SWOT theory. The results of this study indicate that the investigation into the crime of weighted theft by the Satreskrim of the Karanganyar Police is not in accordance with the applicable regulations, the factors that influence the process of investigating the crime of weighted theft by the Satreskrim of the Karanganyar Police include regulations regarding investigations that have not proceeded as they should, investigators have not provide full legal understanding to suspects, lack of implementation of coordination with legal aid agencies and suspects are not aware of the law. The conclusion of the research is that the process of investigating criminal acts of weighted theft at the Karanganyar Police is not optimal because the investigation is not in accordance with applicable regulations. Legal factors, law enforcers, facilities and amenities, and the community have an influence on the process of investigating the crime of weighted theft at the Karanganyar Police Station.
Keywords: weighted theft; investigation; human rights